EFFECTS OF NATURAL EXTRACT OF CELERY LEAVES ON THE KIDNEYS OF WHITE RATS (Rattus novergicus) AFTER ASPIRIN INDUCTION - Indriana, Edni; Titrawani, Titrawani (Jurnal Pendidikan Matematika dan IPA, 2022)
Herbal plants can be used as a treatment option, including the treatment of kidney disease. The administration of herbal remedies such as celery is a more natural and safe treatment healing alternative. The study aims to determine the effect of celery extract in repairing the damage to the kidney cells of aspirin-induced white mice. This study used a completely randomized design (CRD) consisting of 5 groups with 3 replications: K- (aspirin 12.6 mg/kg BW), K+ (feed normal), P1 (celery extract 200 mg/kg BW + aspirin 12.6 mg/kg BW), P2 (celery extract 100mg/kg BW + aspirin 12.6 mg/kg BW) and P3 (celery extract 50 mg/kg BW) + aspirin 12.6 mg/kg BW). From the results of observations on kidney histology of rats after giving aspirin, it is known that there is damage to the nucleus of cells undergoing pyknosis and swelling of the glomerulus, which is characterized by narrowing of the Bowman's space.  This suggests that the celery extract at a stratified dose may affect the histopathological kidney of aspirin-induced mice.